Esperança no cotidiano: da escatologia cristã à escatologia de Libertação - BELTRAN ACERO, Carlos José (2011)
The recovery of eschatology as the motor and the center of Christian theology has its apex in the work of Jürgen Moltmann, Theology of Hope (1964). In Latin America, little was done about a re-elaboration of eschatology and its implications for systematic theology in a Latin American theological method. Among the few works we have the book of João Batista Libânio and Maria Clara Bingemer, Christian Eschatology (1985). Both authors address the theme of Christian hope from different perspectives. After describing systematically the eschatologies of these two authors, we seek to determine to what extent the focus of these authors contributes or not as a theoretical tool to read the world and to illuminate a praxis engaged with change and transformation of oppressive structures in society. In the end, it is about rethinking eschatology in its relevance to the daily life of people.(AU)